Elevated maternal temperature enhances offspring disease resistance in Daphnia magna. (2nd December 2013) - Garbutt, Jennie S.; Scholefield, Jennifer A.; Vale, Pedro F.; Little, Tom J.; Martin, Lynn
Summary Maternal effects are increasingly recognized to impact upon infectious diseases. Stressful environmental conditions that coincide with high infection prevalence are potential cues for adaptive maternal effects on offspring resistance to infection. We studied how maternal temperature (15 °C, 20 °C and 25 °C), as well as maternal food availability (high and low food) influenced the ability of the crustacean, Daphnia magna, to resist its bacterial parasite, Pasteuria ramosa. Mothers held at a higher temperature and mothers fed a restricted diet produced offspring that were more resistant to P. ramosa infection. Maternal temperature also influenced the progression of disease in infected offspring. Parasite spore production and host reproduction were affected by maternal temperature, but these effects differed in the two genotypes used. As Daphnia populations experience regular summer epidemics of P. ramosa, temperature may be an environmental signal of infection risk. Thus, the enhanced resistance we observed under stressful food and temperature is conceivably an adaptation to looming epidemics. Thus, this study identifies novel ways in which the maternal environment impacts upon disease resistance and indicates how phenotypic plasticity might both alter co‐evolution and mitigate epidemics driven by environmental change in a wide range of taxa.